”Uten oss går det ikke” – pårørendes erfaringer med psykisk krise - Borg, Marit; Haugård, Ellinor; Karlsson, Bengt (Nordisk tidsskrift for helseforskning, 2012)
Summary “Without us there is nothing” – relatives experiences of mental health crisis.As Norway moves toward the provision of home-based crisis response, more knowledge is needed about understandings of mental health crisis and effective ways of addressing crises within the home context. The objective of this study was to explore and learn from relatives’ experiences about the subjective meanings of crisis and meaningful and efficient crisis support. Findings were clustered into three themes: 1) Experiences of rejection and responsibility, 2) Living with contradictions, and 3) The art of balancing openness. The findings indicate that it is crucial to transform the recent knowledge about family and social network involvement in crisis resolution into a new practice. Family and network expect to be treated with reciprocal trust and respect by services, and guidance on how they can help. Least of all they accept discharge to the family without any information or guidance. Neither do they want to be deprived the opportunity to tell their part of the story.
Keywords: Mental health care; relatives; experience-based knowledge; mental health crisis; mental health services; Psykisk helsearbeid; pårørende; erfaringsbasert kunnskap; psykisk krise; psykiske helsetjenester